Alternative responses to fungal attack on a metalliferous soil: Phytohormone levels and structural changes in Silene paradoxa L. growing under copper stress. (September 2019) - Papini, Alessio; Luti, Simone; Colzi, Ilaria; Mazzoli, Lorenzo; Giorni, Elisabetta; Pazzagli, Luigia; Gonnelli, Cristina
Highlights: Metallicolous and nonmetallicolous Silene paradoxa populations were compared. Plants were exposed to cerato-platanin in presence/absence of Cu in culture media. Hormone signaling after PAMP exposition was different in the two populations. Stress-induced autophagy was more evident in nonmetallicolous plants. Abstract: In this work, a non-metallicolous and a metallicolous population of S. paradoxa were exposed to copper excess and fungal elicitation, and investigated for phytohormone production and cytological alterations. Under the stress applied separately and in combination, S. paradoxa plants varied phytohormone concentration in a population-specific way, suggesting a different signalling in response to biotic and abiotic stimuli according to the environment of origin. Generally, the stress responses consisted in increased levels of salicylic acid, auxin, and gibberellin in the non-metallicolous population, and of jasmonic and abscisic acid in the metallicolous one. Interestingly, the metallicolous population increased the level of such phytohormones following exposure to the fungal elicitor only in the presence of copper. This alternative hormonal signalling could derive from the incompatibility between the ordinary ROS-mediated response to pathogens and the acquired mechanisms that prevent oxidative stress in the population from the metal-rich soil. Furthermore, stress-induced autophagic phenomena were more evident in the non-metallicolous plants than in the metallicolous ones, suggesting that the adaptation to the metalliferous environment has also affected autophagy intensity and signalling in response to copper excess and fungal elicitation.